THE EFFECTIVENESS OF BIRTHING BALL AS COMPLAINTS REDUCTION PHYSICAL ON PREGNANT MOTHERS TO PREPARATION FOR DELIVERY IN DEBY MATERNAL HOUSE IN MEDAN CITY - Riska Susanti Pasaribu; Deby Cintya Yun; Ridesman Ridesman (International Journal of Midwifery Research, 2022)
Labor is the process of the baby, placenta, amniotic membranes coming out of the mother's uterus, gestational age at term (37 weeks) without any complications, labor pain causes frustration, trauma that can occur to the mother. Labor pain can be treated in an effective way because pain accompanied by a stress reaction will have harmful side effects for the mother and fetus. This study aims to develop knowledge in the field of midwifery knowledge and can educate mothers in labor to reduce physical complaints and can speed up the delivery process. The research method used is a quasi-experimental pre-test and post-test research design, which is a research design to analyze the effectiveness of the Birthing Ball as a Reduction of Physical Complaints in Pregnant Women on Childbirth Preparation. Sampling using consecutive sampling technique, analysis using independent t test to compare the values ​​in the intervention group and control group. There is an effect of the implementation of the birthing ball as a reduction in physical complaints with a value of p = 0.001 meaning p <0.05 and there is a difference in the process of labor taking place faster in the first stage of the active phase in the intervention group where birthing balls are carried out 2-3 times a day during the final trimester compared to the group. control. The birthing ball should be done every day during the third trimester of pregnancy to reduce the physical complaints of pregnancy and speed up the delivery process.